MEASUREMENT OF NITRIC OXIDE IN EXHALED AIR AS AN INSTRUMENT OF MONITORING BASIC THERAPY EFFICACY IN CHILDREN WITH BRONCHIAL ASTHMA - S.E. Tsyplenkova (Union of pediatricians of Russia, 2006)
An individual approach to prescribing the most effective therapy for bronchial asthma is one of the actual problems of pediatric. It necessitates the development of new diagnostic markers of disease activity. a method of nitric oxide (no) measurement in exhaled air has been widely promoted to satisfy the necessity. The purpose of this study was to evaluate the measurement of no levels in exhaled air as an instrument to assess the efficacy of basic therapy for bronchial asthma in children and compare the method with those traditionally used for patient evaluation in pediatric pulmonological clinic. We examined 200 children aged 6:17 with varying severity of asthma course. all children underwent an on:line measurement of nitric oxide level in exhaled air by means of hemiluminescent gas analyzer 280i (sievers, usa) and body plethysmography ("master screen", jaeger, germany).A statistically significant increase in no levels has correlated with disease severity, clinical course and amount of administered treatment. The concentration of no has corresponded to asthma severity in concurrence with respiratory function changes and elevation of total sera Ige. In some patients the increase of no in exhales air has anticipated clinical and functional features of asthma exacerbation, thus providing basis for therapy review. Anti-inflamatory agents have produced dose:dependent decrease of no concentration in exhaled air. The study has proven that the measurement of no in exhaled air could help to optimize therapy individually and to stabilize patient's condition in shorter periods than those obtained using standard therapy regimes.Key words: children, bronchial asthma, nitric oxide, therapeutic efficacy monitoring.